Analisis Pendapatan Petani Jagung Manis dalam Penggunaan Pupuk Kompos di Desa Seuneubok Dalam - Cut Putri Ayu Andira Andira; Bayu Eka Wicaksana (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
The use of compost fertilizer is an important strategy in increasing the productivity and income of sweet corn farmers in a sustainable manner. This study aims to analyze the income of sweet corn farmers using compost fertilizer in Seuneubok Dalam Village, Idi Tunong Subdistrict, East Aceh Regency. The study uses a quantitative descriptive approach with a farm income analysis method. The research population consisted of 134 sweet corn farmers who were members of eight farmer groups, with a total of 57 farmers selected as respondents using the Slovin formula at a tolerance level of 10% through simple random sampling. The data used included primary and secondary data collected through surveys, interviews, and documentation. The results showed that the use of compost fertilizer was able to improve the quality and quantity of sweet corn production, as indicated by an increase in the average cob weight from 153 grams to 200 grams and an increase in production from 5,130 kg/ha to 6,560 kg/ha. The improvement in crop quality resulted in an increase in the selling price from IDR 1,400/kg to IDR 2,000/kg, thereby increasing farmers' income from IDR 7,182,000/ha to IDR 13,120,000/ha. The total production cost of farming is IDR 3,063,048/ha, resulting in a net income for farmers of IDR 10,056,952/ha per planting season. The results of the study show that the use of compost contributes positively to increasing the income of sweet corn farmers and supports the efficiency and sustainability of farming.